2018
DOI: 10.1007/s13238-018-0581-0
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb chromobox Cbx2 enhances antiviral innate immunity by promoting Jmjd3-mediated demethylation of H3K27 at the Ifnb promoter

Abstract: Polycomb chromobox (CBX) proteins regulate gene transcription by maintaining chromatin states, which guide a variety of biological processes. Now, epigenetic regulation of innate immune response is an emerging field. However, the role of CBX proteins in innate immunity remains unclear. We confirmed that the expression of CBX family proteins, especially Cbx2, was decreased in macrophages upon viral infection, and then we investigated the role of Cbx2 in the antiviral immune response. Silencing or knockdown of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Furthermore, polycomb chromobox (CBX) proteins, especially CBX2 were down-regulated in macrophage upon viral infection. Cbx2 knockdown or silencing inhibited IFN-β production and played a critical role in antiviral innate immunity [ 19 ]. On the basis of the aforementioned findings, the specific TFs for promoters encoding may be readily translated to clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, polycomb chromobox (CBX) proteins, especially CBX2 were down-regulated in macrophage upon viral infection. Cbx2 knockdown or silencing inhibited IFN-β production and played a critical role in antiviral innate immunity [ 19 ]. On the basis of the aforementioned findings, the specific TFs for promoters encoding may be readily translated to clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…JMJD3 may play the opposite effect in the epigenetic regulation of different types of infections. JMJD3 enhanced the production of type I interferon in macrophage to inhibit the infection of VSV (vesicular stomatitis virus) and HSV (herpes simplex virus) (Sun et al 2019); JMJD3 activated viral immediate early (IE) gene expression, which was crucial in anti-viral infection to inhibit human cytomegalovirus (hCMV) viral infection (Gan et al 2017); In ameba infection, up-regulation of JMJD3 expression continued to increase bone marrow colony stimulating factor 2 receptor alpha (Csf2ra) expression and granulocyte monocyte precursors (GMPs), and prevented amoebic infection (Burgess et al 2016); JMJD3 was found to enhance the transcription efficiency of HBV via its interaction with C/EBPα (Chen et al 2016); JMJD3 promoted the mycobacterial infection by assisting foamy macrophages (FM)s harbor lipid bodies generation (Holla et al 2016); JMJD3 conducived to Kaposi’s sarcoma associated herpesvirus (KSHV) invasion by noncoding polyadenylated transcript PAN RNA retained in the nucleus of host cells in infection, and decreasing the repressive H3K27me3 mark at the lytic switch protein gene promoter (Rossetto and Pari 2012). These findings indicate that JMJD3 mediate pathogen infection mainly through regulating the expression of key infection-related genes or increasing the production of key infection-related cytokines through various pathways, and provides insights into potential targeted therapeutic avenues for the treatment of infectious diseases.…”
Section: Jmjd3 In Infectious Diseasesmentioning
confidence: 99%
“…Jumonji domain-containing 3, a member of JMJD protein family, catalyzes the removal of methyl group from H3K27me3 and regulates gene transcription. JMJD3 participated a wide range of disease processes including immune diseases (Chen et al, 2018), cancer (Ramadoss et al, 2012), infectious diseases (Sun et al, 2019), aging related diseases (Salminen et al, 2014;Tamgue and Lei, 2017), and development diseases (Park et al, 2014). By regulating the expression of matrix metalloproteinase-3 (MMP-3) and MMP-9, JMJD3 was reported to mediate blood-spinal cord barrier disruption (Lee et al, 2016).…”
Section: Discussionmentioning
confidence: 99%